Socialization of Waste Management Based on the Principles of Reduce, Reuse And Recycle (3r) to Increase Community Knowledge and Skills Regarding Household Waste Management - Pambudi, Yonathan Suryo; Sudaryantiningsih, Cicik; Lolo, Elvis Umbu; Widianto, Widianto (PT FORMOSA CENDEKIA GLOBAL, 2024)
This activity was carried out through the Community Service program by lecturers from Solo Christian Technology University (UKTS) in Ingasrejo Hamlet, Plesungan Village, Gondangrejo District, Karanganyar, Indonesia. The methods used include a pre-test, providing socialization material, and a post-test to evaluate the increase in participants' knowledge. Participation in this activity involved 20 people consisting of Rukun Warga (RW) administrators, Rukun Tetangga (RT) administrators, women from the Family Welfare Development Management (PKK), and local Youth Organization (Karangtaruna) administrators. The pre-test results showed that only 28.75% of participants had good knowledge of the 3R principles, while 42.5% were in the poor category. After socialization, the post-test results showed a significant increase where 73.75% of participants were in the good category and no participants were in the poor category.